In vitro activity of ceftolozane/tazobactam against ESBL-producing enterobacterales in China: SMART 2016–2019 - Wei Yu; Hui Zhang; Yingchun Xu; Ying Zhu; Peiyao Jia; Yue Kang; Qiwen Yang (Journal of Global Antimicrobial Resistance)
Objectives: To evaluate the in vitro susceptibility of ESBL-producing Enterobacterales isolates to ceftolozane/tazobactam (C/T), a combination of tazobactam (a ß-lactamase inhibitor) and a new antipseudomonal cephalosporin. Methods: From 2016 to 2019, susceptibilities of 10,545 Enterobacterales isolated from intra-abdominal, urinary tract, respiratory tract and bloodstream infections to C/T and 11 other antimicrobial agents were analyzed. Non-ESBL-producing isolates were included for comparative analysis to provide a comprehensive susceptibility profile. Results: Among 10,545 isolated Enterobacterales, 54.6% were ESBL producers. The ESBL-positive rates for E. coli (4984/10,545, 47.3%) and K. pneumoniae (3606/10,545, 34.2%) were 59.8% and 51.1%, respectively. The susceptibility rate to C/T for all Enterobacterales was 79.5%. For E. coli and K. pneumoniae, the C/T susceptibilities were 89.3% and 68.0%, respectively. For non-ESBL-producing Enterobacterales, susceptibility to C/T was 99.5%. The susceptibility of non-carbapenem-resistant (CR) ESBL-producing Enterobacterales to C/T was 81.0%. The isolation rates of ESBL-positive and carbapenem-resistant Enterobacterales (CRE), CR-E. coli, and CR-K. pneumoniae were 14.3%, 5.6% and 26.8%, respectively. The susceptibility of ESBL-positive CREs to C/T was <20% for most antimicrobials except amikacin (50.4%). The susceptibility of ESBL-positive CR-E. coli to C/T was 28.2. For ESBL-producing CR-K. pneumoniae, susceptibility to most antimicrobials was <10%, except for amikacin (37.4%). Conclusions: The present research underscores the viability of C/T as an alternative to carbapenems for the treatment of ESBL-producing, carbapenem susceptible Enterobacterales. However, the susceptibilities of ESBL-positive CRE to C/T and other studied antimicrobials were consistently below 20%, emphasizing for new innovative treatment strategies.